2009
DOI: 10.1007/s00425-009-0946-y
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene and nitric oxide are involved in maintaining ion homeostasis in Arabidopsis callus under salt stress

Abstract: In the present study, the role of ethylene in nitric oxide (NO)-mediated protection by modulating ion homeostasis in Arabidopsis callus under salt stress was investigated. Results showed that the ethylene-insensitive mutant etr1-3 was more sensitive to salt stress than the wild type (WT). Under 100 mM NaCl, etr1-3 callus displayed a greater electrolyte leakage and Na(+)/K(+) ratio but a lower plasma membrane (PM) H(+)-ATPase activity compared to WT callus. Application of exogenous 1-aminocyclopropane-1-carboxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(77 citation statements)
references
References 60 publications
(84 reference statements)
2
68
1
4
Order By: Relevance
“…Studies involving tobacco seedlings showed that transcriptional activation of ethylene response factor (ERF) in ethylene-signaling process improved salt stress tolerance by decreasing ROS accumulation [89]. Treatment of Arabidopsis callus with 100 mM NaCl triggered the accumulation of NO that promoted ET emission, resulting in increased expression of the plasma membrane H + -ATPase genes [90]. Hence, both NO and ET participate in up-regulation of plasma membrane H + -ATPase that modulates ion homeostasis for improved salt tolerance.…”
Section: No-phytohormone Cross Talk Under Salinity Stressmentioning
confidence: 99%
“…Studies involving tobacco seedlings showed that transcriptional activation of ethylene response factor (ERF) in ethylene-signaling process improved salt stress tolerance by decreasing ROS accumulation [89]. Treatment of Arabidopsis callus with 100 mM NaCl triggered the accumulation of NO that promoted ET emission, resulting in increased expression of the plasma membrane H + -ATPase genes [90]. Hence, both NO and ET participate in up-regulation of plasma membrane H + -ATPase that modulates ion homeostasis for improved salt tolerance.…”
Section: No-phytohormone Cross Talk Under Salinity Stressmentioning
confidence: 99%
“…Thus, under slight drought IAA level had no significant change, after moderate drought stress IAA level was reduced to about 81%, and after severe drought stress the level of this Aux was reduced to 72% of the control. The salinity stress induces an Aux accumulation in Arabidopsis and its redistribution to the root tip, resulting in the primary root growth inhibition, a marked reduction in lateral root primordia formation, and significantly increases in the elongation of existing lateral roots [71] (Figure 2). Thus, these results suggest that Aux transport appears to be essential for the adaptive remodeling of root system architecture under salinity.…”
Section: Effect Of Aux On Plant Growth Responses Under Drought and Samentioning
confidence: 99%
“…NO production is altered when plants are subjected to abiotic or biotic stresses (13,14). High salt, a major environmental factor that limits agriculture yield, induces a quick endogenous NO accumulation in plants (15,16), and triggers enhanced Na + influx and reduced K + absorption in the root (17). Both endogenously produced NO and exogenously applied NO have been proposed to enhance plant salt tolerance (18-21) by attenuating high saltinduced increases in the Na + to K + ratio.…”
mentioning
confidence: 99%